2017
DOI: 10.1186/s13662-017-1328-6
|View full text |Cite
|
Sign up to set email alerts
|

An exponential B-spline collocation method for the fractional sub-diffusion equation

Abstract: In this article, we propose an exponential B-spline approach to obtain approximate solutions for the fractional sub-diffusion equation of Caputo type. The presented method is established via a uniform nodal collocation strategy by using an exponential B-spline based interpolation in conjunction with an effective finite difference scheme in time. The unique solvability is rigorously proved. The unconditional stability is well illustrated via a procedure closely resembling the classic von Neumann technique. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…McCartin also showed that the exponential splines accept a basis of B-splines. They are used in approximating the solutions of various classes of problems in differential equations [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…McCartin also showed that the exponential splines accept a basis of B-splines. They are used in approximating the solutions of various classes of problems in differential equations [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Several differential equations have been solved by utilizing this method. [24][25][26][27][28][29][30] Using this technique, one can avail of the solution even between nodes, which is an advantage over the finite difference scheme. There is no requirement to compute quadratures as in the finite element technique.…”
Section: Introductionmentioning
confidence: 99%
“…The exponential B‐spline technique is based on piece‐wise non‐polynomial functions and was developed by McCartin, 23 and it is the generalization of the cubic spline. Several differential equations have been solved by utilizing this method 24–30 . Using this technique, one can avail of the solution even between nodes, which is an advantage over the finite difference scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Zahra and Elkholy [13] use cubic splines to represent a numerical solution of fractional differential equations. Nonclassical diffusion problems by Ismail et al [14], advection-diffusion problems by Nazir et al [15], and fractional subdiffusion equation by Zhu et al [16] are solved by using B-spline collocation methods. In recent times, Hashmi et al [17,18] has solved Hunter Saxton equation and space fractional PDE by cubic trigonometric and hybrid B-spline method.…”
Section: Introductionmentioning
confidence: 99%